2015
DOI: 10.1189/jlb.3a0215-041rr
|View full text |Cite
|
Sign up to set email alerts
|

IFN-λ is able to augment TLR-mediated activation and subsequent function of primary human B cells

Abstract: During the past decade, increased emphasis has been placed on finding alternatives to IFN-α-based therapies. One such alternative, IFN-λ, has shown therapeutic promise in a variety of diseases, but research of this family of cytokines has been primarily focused on their antiviral activities. The goal of the present study was to investigate the role of IFN-λ in the regulation and modulation of B cell function. We show that, similar to IFN-α, IFN-λ1 is able to augment TLR-mediated B cell activation, partially at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 41 publications
2
59
0
Order By: Relevance
“…Generally, the role of IFN-λ on B cells was only modestly studied. One recent article by de Groen et al demonstrated that both naive and memory B cells express IFNLR1 mRNA and that IFN-λ1 can activate B cells (83). Treatment of B cells with IFN-λ1 led to increased expression of ISGs (Mx1 and OAS1) as well as increased expression of TLR7.…”
Section: Ifn-λ Interaction With Hematopoietic Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the role of IFN-λ on B cells was only modestly studied. One recent article by de Groen et al demonstrated that both naive and memory B cells express IFNLR1 mRNA and that IFN-λ1 can activate B cells (83). Treatment of B cells with IFN-λ1 led to increased expression of ISGs (Mx1 and OAS1) as well as increased expression of TLR7.…”
Section: Ifn-λ Interaction With Hematopoietic Cellsmentioning
confidence: 99%
“…Finally, IFN-λ1 stimulation increased the proliferation of B cells stimulated with TLR7/8 agonist. However, after TLR2 or TLR9 stimulation, IFN-λ1 had no effect on the antibody production or proliferation (83). Globally, this study suggests that IFN-λ1 can enhance B cell response, but only under certain stimulation conditions.…”
Section: Ifn-λ Interaction With Hematopoietic Cellsmentioning
confidence: 99%
“…CD19 + B cells stimulated with IL‐29 could significantly up‐regulate IFN‐stimulated genes myxovirus resistance‐1 (Mx1) and OAS1 expression. IL‐29 stimulation on CD19 + B cells also up‐regulated TLR7 expression . Intriguingly, the combination of IL‐29 with R848 enhanced TLR7/8‐mediated IgG and IgM production, and the production of R848‐mediated IL‐6 on treated CD19 + B cells, implying the role of IL‐29 to regulate TLR7/8‐triggered cytokine secretion .…”
Section: Biologic Functions Of Il‐29mentioning
confidence: 94%
“…Human CD27 − naive and CD27 + B cells stimulated by IL‐29 alone or in combination with the TLR7/8 ligand R848 significantly up‐regulated the marker CD69, indicating that both naive and memory B cell populations were responsive to IL‐29 stimulation . CD19 + B cells stimulated with IL‐29 could significantly up‐regulate IFN‐stimulated genes myxovirus resistance‐1 (Mx1) and OAS1 expression.…”
Section: Biologic Functions Of Il‐29mentioning
confidence: 99%
See 1 more Smart Citation